Evaluation of BacT/Alert 3D Liquid Culture System for Recovery of Mycobacteria from Clinical Specimens Using Sodium Dodecyl (Lauryl) Sulfate-NaOH Decontamination - Carricajo, A. (American Society for Microbiology, 2001)
A total of 52 mycobacterial isolates were recovered from 1,197 clinical specimens decontaminated by a sodium dodecyl (lauryl) sulfate (SDS)-NaOH protocol. Of these, 94% were recovered with the BacT/Alert 3D system (Organon Teknika, Durham, N.C.) and 79% were recovered on Löwenstein-Jensen (LJ) medium. Mean times to detection of organisms of the Mycobacterium tuberculosis complex (n = 47) were 22.8 days with LJ medium and 16.2 days with the system. The BacT/Alert 3D system is a rapid and efficient detection system which can be used with an SDS-NaOH decontamination procedure.